2019
DOI: 10.1111/bpa.12805
|View full text |Cite|
|
Sign up to set email alerts
|

The anatomy and metabolome of the lymphatic system in the brain in health and disease

Abstract: Recent studies have demonstrated that the brain is equipped with a lymphatic drainage system that is actively involved in parenchymal waste clearance, brain homeostasis and immune regulation. However, the exact anatomic drainage routes of brain lymph fluid (BLF) remain elusive, hampering the physiological study and clinical application of this system. In this study, we systematically dissected the anatomy of the BLF pathways in a rat model. Moreover, we developed a protocol to collect BLF from the afferent lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 62 publications
(105 reference statements)
0
15
0
Order By: Relevance
“…All rats were purchased from the Experimental Animal Center of Huazhong Agricultural University. In order to construct a GBM rat model, C6-luc cells (1 × 10 6 ) in 10 μl of F-12K medium were stereotactically injected into the left striatum of Wistar male rats (180–220 g) 34 .…”
Section: Methodsmentioning
confidence: 99%
“…All rats were purchased from the Experimental Animal Center of Huazhong Agricultural University. In order to construct a GBM rat model, C6-luc cells (1 × 10 6 ) in 10 μl of F-12K medium were stereotactically injected into the left striatum of Wistar male rats (180–220 g) 34 .…”
Section: Methodsmentioning
confidence: 99%
“…He et al [79] have developed an interesting approach for sampling brain lymph fluid from the afferent lymph vessels of deep cervical lymph nodes. A different analyte profile may result from this fluid compared to the CSF sampled from the usual sites (e.g., lumbar puncture).…”
Section: Csf Analysismentioning
confidence: 99%
“…Recent studies have confirmed three outflow pathways of CSF in healthy mice and rats (2,3,(6)(7)(8)(30)(31)(32). However, in the glioma model, CSF drainage along the exiting cranial nerves and downstream lymph nodes was shown to be reduced (7).…”
Section: Introductionmentioning
confidence: 98%
“…Traditional theories of CSF drainage suggest that CSF is generated by the ventricles and flows into the subarachnoid space, absorbed by the arachnoid particles and arachnoid villi, and carried to the venous sinuses (1)(2)(3)(4)(5). However, recent studies have revealed other CSF exit pathways (1): along the nerves, such as the olfactory and spinal nerves, leaving the skull to reach the cervical and spinal lymph nodes (2,3,6,7); flowing out through the "glymphatic system" (8)(9)(10)(11)(12)(13). In 2012, Iliff et al (8) discovered the "glymphatic system" in the mouse brain for the first time.…”
Section: Introductionmentioning
confidence: 99%